Evaluación del potencial de producción de metano con diferentes tipos de residuos sólidos y líquidos orgánicos rurales (2021)
Generally, the main source of obtaining energy in rural areas corresponds to non-renewable resources such as coal, oil and natural gas, however, because the demand is increasing and the resources to obtain them are decreasing rapidly, the problem current information on energy is becoming more and more evident, which makes it essential to find out about other potential sources of energy generation. This is why, taking into account the large amount of solid and liquid organic waste that is generated in these areas, they can be potential sources of biogas production. Biogas, as a renewable energy source, has generated great interest in recent years, being perhaps one of the most easily developed technologies, especially in rural sectors.